Effect of Quality of Good Corporate Governance Disclosure, Leverage and Firm Size on Profitability of Isalmic Commercial Banks - Harisa, Enni; Adam, Mohamad; Meutia, Inten (International Journal of Economics and Financial Issues, 2019)
The purpose of this study was to determine the effect of the quality of disclosure of good corporate governance (GCG), leverage, and firm size on profitability in Islamic commercial banks in Indonesia and Malaysia. The data used in this study were obtained from the website of each bank in the period 2011-2017 with a total sample of 16 Islamic commercial banks. The data analysis technique used in this study is panel data regression analysis. The results showed that the quality of GCG disclosure and leverage had an effect on profitability while the firm size variable had an effect on profitability. Keywords: Islamic commercial bank; quality of GCG disclosure; leverage; firm size; profitability JEL Classifications: M4, G38, G2, G3 DOI: https://doi.org/10.32479/ijefi.8157